Hypoxia Impairs Muscle Function and Reduces Myotube Size in Tissue Engineered Skeletal Muscle. Issue 9 (15th May 2017) - Martin, Neil R.W.; Aguilar‐Agon, Kathyrn; Robinson, George P.; Player, Darren J.; Turner, Mark C.; Myers, Stephen D.; Lewis, Mark P.
ABSTRACT: Contemporary tissue engineered skeletal muscle models display a high degree of physiological accuracy compared with native tissue, and therefore may be excellent platforms to understand how various pathologies affect skeletal muscle. Chronic obstructive pulmonary disease (COPD) is a lung disease which causes tissue hypoxia and is characterized by muscle fiber atrophy and impaired muscle function. In the present study we exposed engineered skeletal muscle to varying levels of oxygen (O2 ; 21–1%) for 24 h in order to see if a COPD like muscle phenotype could be recreated in vitro, and if so, at what degree of hypoxia this occurred. Maximal contractile force was attenuated in hypoxia compared to 21% O2 ; with culture at 5% and 1% O2 causing the most pronounced effects with 62% and 56% decrements in force, respectively. Furthermore at these levels of O2, myotubes within the engineered muscles displayed significant atrophy which was not seen at higher O2 levels. At the molecular level we observed increases in mRNA expression of MuRF‐1 only at 1% O2 whereas MAFbx expression was elevated at 10%, 5%, and 1% O2 . In addition, p70S6 kinase phosphorylation (a downstream effector of mTORC1) was reduced when engineered muscle was cultured at 1% O2, with no significant changes seen above this O2 level. Overall, these data suggest that engineered muscle exposed to O2 levels of ≤5% adapts in a manner similar to that seen in COPD patients, and thus may provide a novel model for further understanding muscle wasting associated with tissue hypoxia. J. Cell. Biochem. 118: 2599–2605, 2017. © 2017 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals, Inc. Abstract : Tissue engineered skeletal muscle structurally and phenotypically provides a valid model of native skeletal muscle, however there is little data which has identified if it is capable of modeling alterations in muscle tissue associated with disease states, for example, COPD. In the present work, tissue engineered skeletal muscle was exposed to various levels of hypoxia for the final 24 h of culture in order to ascertain if engineered muscle responds to a hypoxic stimulus in a manner akin to that seen in COPD. Our results show that low levels of oxygen drive a loss of muscle function and size, underpinned by augmented catabolic and attenuated anabolic signaling; thus simulating the atrophic phenotype associated with COPD.